Simultaneous optimization for continuous improvement and cost reduction in processes (2006)
Many optimization problems are characterized by the flexibility to establish utility between the objective functions. The experimental strategy plays an important role in generating these objective functions, in addition, it has been conveniently applied to reduce quality costs and in the continuous improvement of the quality of processes and products. It is common to find many industrial applications with several responses whose purpose is to achieve the overall quality of a product, so it is necessary to simultaneously optimize the responses of interest. In essence, the problem of optimization of several responses involves selecting a set of independent variables such conditions or that result in a product or service appropriate. That is, it is desired to select the levels of the independent variables that optimize all the answers at the same time.